2019
DOI: 10.1021/acsami.9b18185
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Fiber-Based ZnO Nanowire Network Ultraviolet Photodetector Enabled by the Synergism between Interface and Surface Gating Effects

Abstract: A flexible UV photodetector with a high on/off ratio is extremely important for environmental sensing, optical communication, and flexible optoelectronic devices. In this work, a flexible fiber-based UV photodetector with an ultrahigh on/off ratio is developed by utilizing the synergism between interface and surface gating effects on a ZnO nanowire network structure. The synergism between two gating effects is realized by the interplay between surface band bending and the Fermi level through the nanowire netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Synthesis of ZnO nano/microwires. ZnO nano/microwires used in the experiment were synthesized using a chemical vapor deposition (CVD) method through a vapor-solid process 44 . First, 2.0 g of ZnO powder and 0.4 g of graphite powder were ground in an agate mortar to obtain a uniform mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of ZnO nano/microwires. ZnO nano/microwires used in the experiment were synthesized using a chemical vapor deposition (CVD) method through a vapor-solid process 44 . First, 2.0 g of ZnO powder and 0.4 g of graphite powder were ground in an agate mortar to obtain a uniform mixture.…”
Section: Methodsmentioning
confidence: 99%
“…3c, d and S3. Compared with the pristine ZnO device, the τ rise and τ decay of the device Al/ZnO-300 decreased to ~ 0.79 s and ~ 0.24 s. The response speed of the Al/ZnO heterostructure photodetector was apparently superior to previously reported ZnO-based UV photodetectors [4,[30][31][32], and was even faster than our previously reported Cu/ZnO hybrid architecture photodetectors [1]. The light intensity dependence on the I ph was compared for the Al/ZnO heterostructure photodetector at an identical bias of 10 V as shown in Fig.…”
Section: Annealing Temperature Effect On Device Performancementioning
confidence: 69%
“…Meng et al reported a fiber-based ZnO NW network UV photodetector. The interface and surface gating effects were considered to investigate the optoelectronic performance of the photodetector [19]. Due to the one-dimensional size effect, ZnO NW would be completely depleted, which resulted in a large distance between the Fermi level and conduction band and a dramatic decrease of carrier density by several orders of magnitude in dark.…”
Section: A Conversional Zno Nws/nrs-based Ultraviolet Photodetectorsmentioning
confidence: 99%
“…The current-voltage results showed that the photocurrent of the as-fabricated UV photodetector based on ZnO/Cu x O core-shell NW structure had a significant increase because of the type-II band alignment. Under UV illumination with a wavelength of 365 nm and at a bias of 1 V, the rise time and the recovery time were 43 s, and the responsivity, the external quantum efficiency and the detectivity were 43.95 A/W, 149.3% and 75.51×10 19 Jones, respectively. The results indicate that a type-II band alignment is formed at the heterointerface of ZnO/Cu x O.…”
Section: ) Core-shell-based Heterojunction Ultraviolet Photodetectorsmentioning
confidence: 99%